A novel stepped-care approach to weight loss: The role of self-monitoring and health literacy in treatment outcomes. (August 2017) - Carels, Robert A; Selensky, Jennifer C; Rossi, James; Solar, Chelsey; Hlavka, Reid
Abstract: Objectives: The aims of the current study were twofold: 1) examine the effectiveness of an innovative three-step, stepped-care behavioral weight loss treatment, and 2) examine factors that contribute to poor weight loss outcomes and the need for more intensive treatment. Methods: The total sample for the study consisted of 53 individuals (87% female) with MBMI  = 35.6, SDBMI  = 6.4. A three-step, stepped-care treatment approach was implemented over six months. Step 1 included the Diabetes Prevention Program manual adapted for self-administration augmented with monitoring technology shown to facilitate weight loss and participant accountability and engagement. Participants who were unsuccessful at achieving established weight loss goals received stepped-up treatments in 2-month increments beginning at month 2. The stepped progression included the addition of meal replacement at Step 2 and individual counseling concurrent with meal replacement at Step 3. Results: Un-stepped and once stepped participants lost a clinically significant amount of weight (i.e., > 5%), while twice stepped participants lost an insignificant amount of weight. Twice stepped participants were significantly lower in health literacy and self-monitoring frequency. Conclusions: In this investigation, approximately 60% of the participants were able to lose a clinically significant amount of weight utilizing a minimally intensive intervention with little additional support. Regular self-monitoring and high health literacy proved to be significant correlates of success. Highlights: The effectiveness of an innovative three-step, stepped-care behavioral weight loss treatment was examined Factors that contribute to poor weight loss outcomes and the need for more intensive treatment were examined Sixty percent of the participants lost a clinically significant amount of weight receiving a minimally intensive intervention Regular self-monitoring and high health literacy proved to be significant correlates of success